The potential which may lie in discarded, undeveloped or overlooked ideas. Issue 3 (8th June 2015) - Proctor, Tony
Abstract : Purpose: – The purpose of this paper is to examine a particular aspect of the history of the watchmaking industry during the eighteenth century. Attention is drawn to overlooked ideas and inventions and how years later they may become profitable business opportunities for entrepreneurs. The approach adopted allows examination of the development and commercialisation of a watch escapement mechanism, the rack lever, within the context of the development of other escapements. The rack lever was an escapement which was initially overlooked in the early part of the eighteenth century but which many decades later was reinvented and became a commercial success in the early nineteenth century. Design/methodology/approach: – Reference is made to the literature on entrepreneurship and acquisition of knowledge in the eighteenth century and the nature of watchmaking in the same epoch. The literature on entrepreneurship produces a framework for examining the actions that were taken to bring the rack lever escapement to market. The historical context within which the innovations occurred was examined to establish the events and circumstances surrounding the times when commercialisation took place. An account of the commercialisation of the rack lever escapement is presented. Findings: – The entrepreneurial opportunity examined in this article relates to a need to satisfy consumers with a reasonably accurate and reliable portable time piece. The historical context within which commercialisation took place was found to be significant. Attention to the escapement mechanism in watches was identified as the key to improving performance, and the focus of the paper is placed upon how this opportunity was satisfied through the means provided by the rack lever escapement. Alertness to the potential of already discovered but undeveloped ideas appears to be an additional feature behind the entrepreneurial activity. The paper shows that innovation can be a discontinuous process. It also indicates the relevance of modern-day knowledge brokers in facilitating the process of new product innovation. Originality/value: – Entrepreneurship and innovation along with research and development are all intrinsically linked in producing goods and services to satisfy customer wants and needs. Together, they represent a cornerstone which helps to establish a business and maintain its continued survival. Importantly, the development of new products is a key contributor to this end and innovation and entrepreneurship play their part in bringing this about. The paper suggests that new ideas can occur which may be deemed unsuitable for commercialisation at one period in time but which can at a future time be considered a temporary solution to meet an unfulfilled need in the market place. It argues for the case for reserving judgement on new ideas that are not commercialised and ensuring that knowledge of them is kept for posterity and made accessible to future generations.